Faktor-faktor yang mempengaruhi peluang pembangunan kerjaya kumpulan profesional dan eksekutif wanita - Nur Nazihah, Binti Mohd Nazir. (Universiti Malaysia Sarawak (UNIMAS), 2005)
The aim of this research is to ident factors that influencing the opportunity of women's career development characteristics among professional and executives' level. The objectives are (i) to identify relationships between environments factors such as top management support, training programs, mentoring system and peer support with opportunity of women's career development, (ii) to identify relationships between individual factors such as educational level and age with opportunity of women's career development and (iii) to identify the dominants factors that influencing the opportunity of women's career development. Aspects of career development studied in this research are promotions, recognitions, additional responsibility and changes in skills, ability and knowledge. While, factors influencing career development opportunity investigated here are top management support, training programs, mentoring systems, peer support, educational level and age. This research took place in Bank Pertanian Malaysia Kuala Lumpur and comprising 42 professional and executives' women from all departments. Moreover, two statistic tests were used that are Pearson correlation test and Regression correlation test. Finding showed that environments factors (top management support, training programs, mentoring systems and peer support) are significantly relationship with women 's opportunity career development. In additions, individual factors that significantly relationship with women's opportunity career development is age factor. While, the top management support was identified as a dominant factor that significantly relationship with women's opportunity career development. As a result, the top management must support all the activities that are connect with women's career development.